RANCANG BANGUN WEB SERVICE RESELLER PADA TOKO ONLINE KAOS WAYANGAN MENGGUNAKAN REST (Information Technology and Telematics, 2014)
Abstract-- This study examines the data exchange between Kaos Wayangan Reseller App and Client Reseller Website of Kaos Wayangan using web service applications with REST. The main problem is how to make a web service applications that can share information product in Kaos Wayangan with Client Reseller Website of Kaos Wayangan, So that internet users can also saw information that held by Client Reseller Website of Kaos Wayangan. The study produced a web application service with REST protocol that has functions that can be used to share the data between Kaos Wayangan Reseller App with Client Reseller Website of Kaos Wayangan. The main expectation for this application is to bring satisfication for Kaos Wayangan customers,so they can get more customers by displaying its product Kaos Wayangan in client reseller website of Kaos WayanganKeywords: Web Service, REST, PHP, MySQL